LDL oxidation by platelets propagates platelet activation via an oxidative stress-mediated mechanism - Carnevale, Roberto; Bartimoccia, Simona; Nocella, Cristina; Di Santo, Serena; Loffredo, Lorenzo; Illuminati, Giulio; Lombardi, Elisabetta; Boz, Valentina; Del Ben, Maria; De Marco, Luigi; Pignatelli, Pasquale; Violi, Francesco (Atherosclerosis, 2014)
Platelets generate oxidized LDL (ox-LDL) via NOX2-derived oxidative stress. We investigated if once generated by activated platelets ox-LDL can propagate platelet activation. Experiments were performed in platelets from healthy subjects (HS), hyper-cholesterolemic patients and patients with NOX2 hereditary deficiency. Agonist-stimulated platelets from HS added with LDL were associated with a dose-dependent increase of reactive oxidant species and ox-LDL. Agonist-stimulated platelets from HS added with a fixed dose of LDL (57.14 μmol/L) or added with homogenized human atherosclerotic plaque showed enhanced ox-LDL formation (approximately +50% and +30% respectively), which was lowered by a NOX2 inhibitor (approximately −35% and −25% respectively). Compared to HS, ox-LDL production was more pronounced in agonist-stimulated platelet rich plasma (PRP) from hyper-cholesterolemic patients but was almost absent in PRP from NOX2-deficient patients. Platelet aggregation and 8-iso-PGF2α−ΙΙΙ formation increased in LDL-treated washed platelets (+42% and +53% respectively) and PRP (+31% and +53% respectively). Also, LDL enhanced platelet-dependent thrombosis at arterial shear rate (+33%) but did not affect platelet activation in NOX2-deficient patients. Platelet activation by LDL was significantly inhibited by CD36 or LOX1 blocking peptides, two ox-LDL receptor antagonists, or by a NOX2 inhibitor. LDL-added platelets showed increased p38MAPK (+59%) and PKC (+51%) phosphorylation, p47phox translocation to platelet membrane (+34%) and NOX2 activation (+30%), which were inhibited by ox-LDL receptor antagonists. Platelets oxidize LDL, which in turn amplify platelet activation via specific ox-LDL receptors; both effects are mediated by NOX2 activation. •ox-LDL propagate platelet aggregation via interaction with specific receptors.•NOX2 has a key role in propagate platelet aggregation mediated by ox-LDL.•This phenomenon gives new insight in the process of thrombus growth.